Photoactive materials and devices for energy-efficient soft wearable optoelectronic systems - Lee, Sangkyu; Kim, Jihyun; Hannah, Kwon; Son, Donghee; Kim, In Soo; Kang, Joohoon (Elsevier BV, 2023)
Advances in conventional inorganic photoactive materials, such as silicon and III？V compound semiconductors, enabled the development of high-performance and energy-efficient optoelectronic devices (e.g., photodetectors (PDs), light-emitting devices (LEDs), and photovoltaics (PVs)). These devices have recently been considered as essential components for multifunctional wearables that are capable of either providing a long-term stable power supply or visualizing various healthcare indicators in real time. Despite such progress, their rigid and bulky properties pose undesired challenges associated with low signal-to-noise ratios (SNRs) originating from a mechanical modulus mismatch between the skin and device, uncontrolled strain-induced crack propagation, and even long-term discomfort. As alternatives, emerging photoactive materials, such as atomically thin two-dimensional (2D) nanosheets and organic？inorganic halide perovskites with ultra-lightweight, ultrathin, and flexible characteristics have been significantly explored. These materials showed low-power multispectral sensing, effective light-matter coupling, and high compatibility to existing micro-/nano-fabrication technologies even on curved surfaces. Considering stretchability beyond flexibility, numerous research groups have employed well-established mechanical designs including a pre-strain-induced buckled structure with ultrathin layers, neutral-mechanical plane, and rigid-island array configuration with wavy interconnects. Recently, in addition to the above methodology, novel materials strategies regarding intrinsic stretchability and autonomous self-healability were introduced to improve the areal density and electrical/mechanical reliability through removal of serpentine interconnects, as well as adoption of tough damage-resistant polymers with efficient strain dissipation, low glass-transition temperature, and dynamically crosslinked bonds. In this light, the aforementioned methods would be essential to make current flexible photoactive devices intrinsically and durably stretchable. Here, we provide an overview of high-performance photovoltaic/photoemissive materials and devices and their applications to soft wearable energy-efficient optoelectronic systems. In particular, materials synthesis, device fabrication/assembly, and reconfigurable integration used in photoactive material-based wearable modular optoelectronic systems were timely described through a rigorous review of recent results.